The mediating role of job fairness and job burnout between subjective social status and depressive symptoms in Chinese migrant workers: a generational difference analysis - Yuanping Deng; Jiahui Huang; Juan Fang; Shaochang Wu; Yawen Zheng; Li Chen (BMC Public Health)
Abstract Background In China, migrant workers (MWs) constitute a significant vulnerable group that may be highly susceptible to depression. However, there is a lack of empirical research exploring the correlation between subjective social status (SSS) and depressive symptoms among MWs. The objective of this study is to examine the mediating roles of job fairness and job burnout, as well as to investigate potential generational differences in this association. Methods A cross-sectional study was conducted in China among two groups of 1,158 MWs (response rate, 89.08%): first generation migrant workers (FGMWs) and new generation migrant workers (NGMWs). The survey assessed SSS, depressive symptoms, job fairness, and job burnout using a questionnaire. Structural equation model was used to primarily analyze mediating roles of job fairness and job burnout in the relationship between SSS and depressive symptoms, as well as to explore potential generational differences in this association. Results The study findings indicate that SSS significantly predicted higher depressive symptoms among MWs. However, the relationship between SSS and depressive symptoms was mediated by job fairness or job burnout. Notably, the indirect effect of SSS on depressive symptoms through job burnout was significant for FGMWs, but not for NGMWs. Conclusion This study fills a critical gap in understanding the connections between SSS, depressive symptoms, job fairness, and job burnout among MWs in China. It emphasizes the role of job fairness and job burnout as significant mediators that either worsen or alleviate the impact of SSS on depressive symptoms among MWs. Moreover, the findings suggest that the mediation differs significantly between FGMWs and NGMWs. These findings imply the need for different intervention methods to address the depressive symptoms of the two generations of MWs.